Brain volumes and regional cortical thickness in young females with anorexia nervosa. Issue 1 (December 2016) - Fuglset, Tone; Endestad, Tor; Hilland, Eva; Bang, Lasse; Tamnes, Christian; Landrø, Nils; Rø, Øyvind
Abstract Background Anorexia nervosa (AN) is a severe mental illness, with an unknown etiology. Magnetic resonance imaging studies show reduced brain volumes and cortical thickness in patients compared to healthy controls. However, findings are inconsistent, especially concerning the anatomical location and extent of the differences. The purpose of this study was to estimate and compare brain volumes and regional cortical thickness in young females with AN and healthy controls. Methods Magnetic resonance imaging data was acquired from young females with anorexia nervosa (n = 23) and healthy controls (n = 28). Two different scanner sites were used. BMI varied from 13.5 to 20.7 within the patient group, and 11 patients had a BMI > 17.5. FreeSurfer was used to estimate brain volumes and regional cortical thickness. Results There were no differences between groups in total cerebral cortex volume, white matter volume, or lateral ventricle volume. There were also no volume differences in subcortical grey matter structures. However the results showed reduced cortical thickness bilaterally in the superior parietal gyrus, and in the right inferior parietal and superior frontal gyri. Conclusions The functional significance of the findings is undetermined as the majority of the included patients was already partially weight-restored. We discuss whether these regions could be related to predisposing factors of the illness, or whether they are regions that are more vulnerable to starvation, malnutrition or associated processes in AN.